2018
DOI: 10.1101/340901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pediatric Cancer Variant Pathogenicity Information Exchange (PeCanPIE): A Cloud-based Platform for Curating and Classifying Germline Variants

Abstract: 8Variant interpretation in the era of next-generation sequencing (NGS) is challenging. While 1 9

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Twelve hundred genes known to play a role in the pathogenesis of cancer were interrogated using tumor genomic data. Genes were considered in the context of each patient's tumor type and prioritized for review, as previously described (19). Given the potential effects of structural events and gene fusions on protein expression and function, we reported novel events if there was strong sequence support and the structural event or gene fusion involved genes of potential relevance to cancer.…”
Section: Overview Of Somatic Alterationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve hundred genes known to play a role in the pathogenesis of cancer were interrogated using tumor genomic data. Genes were considered in the context of each patient's tumor type and prioritized for review, as previously described (19). Given the potential effects of structural events and gene fusions on protein expression and function, we reported novel events if there was strong sequence support and the structural event or gene fusion involved genes of potential relevance to cancer.…”
Section: Overview Of Somatic Alterationsmentioning
confidence: 99%
“…WGS, WES and RNA-Seq data were aligned and variants called and annotated using previously published algorithms (19,33,69,70) and automated pipeline infrastructure (14).…”
Section: Variant Classification and Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…9418 variants were downloaded from cBioportal (July 15, 2021; Tables S11 and S12). We first analyzed putative pathogenicity of these variants by using PeCanPIE/MedalCeremony (Edmonson et al, 2019), and compared the pathogenicity classification with the ''Driver'' status provided by cBioportal. We found that gene ARID2 has substantial under calling of pathogenicity by cBioportal (15 variants called as driver mutations by CBioportal versus 214 additional variants called as pathogenic/likely pathogenic by PeCanPIE/MedalCeremony).…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…(4) < 10 depth in normal samples; (5) identification as variants in the 1000 Genome East Asian Project (August 2015 release) and not in the COSMIC database (version 70); and (6) identification as variants in the ExAC nonTCGA East Asian database (version 0.3) and not in the COSMIC database. We used Medal Ceremony [27] to annotate driver sites. All the variants were verified by the Integrative Genomics Viewer [28].…”
Section: Whole-exome Sequencing Data Analysismentioning
confidence: 99%